2006
DOI: 10.1007/s11373-006-9139-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms of biotransformation and DNA-repair genes and risk of colorectal cancer in Taiwan

Abstract: The relationship between diet and colorectal cancer has been previously demonstrated and supported with strong epidemiological evidence. The role of genetic polymorphisms has, however, been less well elaborated upon. We conducted a hospital-based case-control study including 727 cases and 736 healthy controls to evaluate the associations of the polymorphic phase-I and -II biotransformations (CYP1A1, CYP1A2, GSTM1, GSTT1, GSTP1, NAT1 and NAT2) and DNA-repair enzymes (XRCC1, XRCC3 and XPD) with the risk of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…The GSTM1 and GSTT1 polymorphisms are the result of the deletion of part of the gene, and this leads to the absence of activity in individuals homozygous for the deletion (null genotype) . The GSTM1 and GSTT1 null genotypes have been associated with increased risk for several cancers including, lung and colorectal cancer (Raimondi et al, 2006;Hosgood et al, 2007;Loft et al, 2007;Yeh et al, 2007). DNA repair is a key human cellular response to DNA-damaging stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…The GSTM1 and GSTT1 polymorphisms are the result of the deletion of part of the gene, and this leads to the absence of activity in individuals homozygous for the deletion (null genotype) . The GSTM1 and GSTT1 null genotypes have been associated with increased risk for several cancers including, lung and colorectal cancer (Raimondi et al, 2006;Hosgood et al, 2007;Loft et al, 2007;Yeh et al, 2007). DNA repair is a key human cellular response to DNA-damaging stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with Economopoulos et al's meta-analysis, our meta-analysis had some differences. Firstly, our meta-analysis included 11 new eligible studies published in Chinese [35-39, 42-44, 47-49] and three new case-control studies published in English [33,34,45], and excluded two studies in Japanese population [52,53] and one study that had overlapping population [20]. At last, we performed this meta-analysis by critically reviewing 19 individual case-control studies (a total of 3,130 CRC cases and 6,423 controls), and the total sample of this new meta-analysis increased to approximately two times (9,553 versus 4,554 [14]).…”
Section: Discussionmentioning
confidence: 99%
“…According to the exclusion criteria, 13 publications were excluded including nine articles containing overlapping data [20][21][22][23][24][25][26][27][28], two about colorectal adenoma [29,30], one for being case-only study [31], and one for not about GSTT1 or GSTM1 polymorphism [32]. At last, data were available from 19 individual casecontrol studies [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] (a total of 3,130 CRC cases and 6,423 controls).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Base on the inclusion criteria, 13 case-control studies with full-text were included in this meta-analysis (Krupa and Blasiak, 2004;Jin et al, 2005;Moreno et al, 2006;Skjelbred et al, 2006;Yeh et al, 2007;Improta et al, 2008;Pardini et al, 2008;Curtin et al, 2009;Canbay et al, 2011;Gil et al, 2012;Zhao et al, 2012;Mucha et al, 2013;Moghtit et al, 2014). The flow chart outlining the criteria used for study selection is shown in Figure 1.…”
Section: Characteristics Of Retrieved Studiesmentioning
confidence: 99%
“…Among the 13 casecontrol studies, there were 8 studies of Caucasians (Krupa and Blasiak, 2004;Skjelbred et al, 2006;Improta et al, 2008;Pardini et al, 2008;Curtin et al, 2009;Canbay et al, 2011;Gil et al, 2012;Mucha et al, 2013) and 5 studies of Asians (Jin et al, 2005;Moreno et al, 2006;Yeh et al, 2007;Zhao et al, 2012;Moghtit et al, 2014). Nine studies were consistent with HWE for the genotype distribution of the controls (Moreno et al, 2006;Skjelbred et al, 2006;Yeh et al, 2007;Improta et al, 2008;Pardini et al, 2008;Curtin et al, 2009;Gil et al, 2012;Mucha et al, 2013;Moghtit et al, 2014), while 4 were not (Krupa and Blasiak, 2004;Jin et al, 2005;Canbay et al, 2011;Zhao et al, 2012). The baseline characteristics and methodological quality of all studies included are summarized in Table 1.…”
Section: Characteristics Of Retrieved Studiesmentioning
confidence: 99%